IMPLEMENTASI METODE USER CENTERED DESIGN PADA APLIKASI KORAN DIGITAL RADAR KARAWANG - Normah, Normah; Zumarniansyah, Ainun; Echtiyar, Agus (INTI Nusa Mandiri, 2026)
The rapid development of digital technology has required print media to adapt in order to remain relevant and competitive in the information era. Radar Karawang, as a local daily newspaper, needs to undergo digital transformation through the development of an Android-based digital newspaper (e-paper) application. This study aims to design the User Interface (UI) and User Experience (UX) of the Radar Karawang digital newspaper application using the User-Centered Design (UCD) method and to evaluate the usability level of the developed application. The UCD method was implemented through several stages, including user needs analysis, prototype or wireframe design, design evaluation based on user feedback, and application implementation. Data were collected through questionnaires distributed to 13 respondents who represented potential users of the application. Usability evaluation was conducted using the System Usability Scale (SUS) method with a Likert scale to measure ease of use, efficiency, and user satisfaction. The evaluation results show that the Radar Karawang digital newspaper application achieved an average SUS score of 74, which falls into the Acceptable category with a Good adjective rating. Nevertheless, this study has several limitations, particularly related to the limited number of respondents and the use of a single usability evaluation method. Therefore, future research is recommended to involve a larger and more diverse group of respondents and to combine other usability evaluation methods to obtain more comprehensive results